Pengaruh Semangat Kerja terhadap Kinerja Perangkat Nagari dalam Pengelolaan Keuangan Nagari di Kabupaten Pesisir Selatan - Yenti, Seprima (JESS (Journal of Education on Social Science); Vol 3 No 2 (2019): Special EditionDO - 10.24036/jess/vol3-iss2/184, 2019)
The purpose of this research is to analyze the effect of work spirit on the performance of nagari apparatus in Nagari financial management in Pesisir Selatan Regency. The background of this research is due to the low work spirit of Nagari apparatus in Koto XI Tarusan and Bayang subdistrict which is still so that it has an impact on Nagari financial management that is not optimal. The method used in this study is a quantitative method with the form of associative research. The population in this study was  of Nagari devices in Koto XI Tarusan and Bayang Subdistrict, totaling 140 respondents. The sample in this study consisted of 126 Nagari devices which were determined using the Slovin formula with an error rate of 5% and the sampling technique using the Proportionate Stratifed Random Sampling technique. Data collection technique in this study are using questionnaires distributed to respondents with measurement using a Likert scale. The data obtained are then analyzed using multiple linear regression. The results of this study indicate that the work spirit variable (simultaneously) has a significant effect on the performance of nagari apparatus in nagari financial management with a significance value of 0,000 and the value of Adjust R Square 0.295. Thus, the influence of work spirit on the performance of nagari devices in managing nagari finances is 29.5%. While the remaining 70.5% is influenced by other variables not examined in this study.